PERBANDINGAN EFEKTIVITAS PEMBERIAN ELECTRIC BLANKET DAN INFUSION WARMER TERHADAP KEJADIAN HIPOTERMI PADA PASIEN POST SECTIO CAESARIA - Pratiwi, Niken Nawang Wulan; Haris, Fahni; Rahmawanto, Rahmawanto (NHM PRESS, 2025)
Background: Sectio Caesaria (CS) is a surgical procedure performed on patients to remove the fetus by opening the abdominal wall and uterine wall. The CS procedure with spinal anesthesia increases the risk of hypothermia. Hypothermia is a condition when the body loses heat faster than heat production with a body temperature below 36.5°C. Hypothermia often causes discomfort in post-CS patients so that effective intervention is needed to treat it. Objective: This study aims to determine the comparative effectiveness of providing electric blankets and infusion warmers on the incidence of hypothermia in CS patients. Method: This study uses quantitative research using a quasi-experimental design. The sample used purposive sampling with many samples taken were 10 post-SC patients and divided into two intervention groups with 1 group containing 5 post-SC patients. Measurements using an axillary thermometer with an intervention time of 15 minutes Results of the study: the results showed a significant difference between the electric Blanket and Infusion Warmer with an increase in temperature before and after the use of the Electric Blanket of 0.8°C and an average increase in temperature before and after the use of the Infusion Warmer of 0.6°C with p = 0.001 (p-value <0.05). Conclusion: this study concluded that there was a significant difference in effectiveness between the use of electric blankets and infusion warmers, the use of electric blankets was more effective in increasing the body temperature of post-sc patients